Dual Role Conflict and Resilience of Working Mothers During the COVID-19 Pandemic: A Phenomenological Study in Ponorogo, Indonesia - Ratnawati, Siti Rohmaturrosyidah; Umah, Restu Yulia Hidayatul (Perkumpulan Alumni dan Santri Mahyajatul Qurro', 2025)
This study discusses the dual role conflict and resilience of working mothers during the Covid-19 pandemic, a new event that has provided many challenges for working mothers in carrying out both their roles in the domestic and public spheres. The Covid-19 pandemic presents extraordinary and unprecedented situations, such as the implementation of work from home, distance learning for schoolchildren, and social restrictions. These conditions created new pressures that were more intense than those before the pandemic. Using qualitative methods and a phenomenological approach, data in this study were collected through in-depth interviews and non-participatory observations and then tested for validity using triangulation techniques and bracketing of interview transcripts. This research was conducted in Ponorogo Regency, East Java, for approximately six months using eight working mothers as research subjects or informants. The results showed that: 1) all eight working mothers experienced dual role conflict in the form of time-based conflict and strain-based conflict, especially during the early days of the Covid-19 pandemic; 2) efforts that have been made by working mothers to be resilient in undergoing both roles during the Covid-19 pandemic represent seven aspects of forming individual resilience, namely, emotion regulation, impulse control, causal analysis, self-efficacy, optimism, empathy, and reaching out. These findings emphasize the need for support for working mothers facing various challenges and difficulties in difficult times, such as a pandemic. The support needed can come from various parties, ranging from family members themselves, especially spouses, friends, and the surrounding environment, to the government.